Computational investigation and experimental validation of the molecular mechanism of Solanecio mannii aqueous roots extract against cervical cancer - Amel Elbasyouni; Mutinda C. Kyama; Hany A. El-Shemy; Peter G. Mwitari (PLoS ONE, 2025)
Cervical cancer remains one of the leading causes of cancer-related mortality among women worldwide, particularly in low- and middle-income countries, highlighting the need for improved strategies in treatment and management. This study aimed to investigate the anti-cervical cancer potential and molecular mechanisms of Solanecio mannii (S. mannii) aqueous extract using a “multi-compound, multi-target, multi-pathway” approach, integrating both computational and experimental methods. The metabolomics profile of the extract was analysed, and its selective cytotoxicity was assessed against human cervical cancer cell lines (HeLa cells) using the CCK8 assay. A network pharmacology approach identified potential molecular targets and pathways, which was complemented by molecular docking and dynamic simulation. The expression levels of key targets were validated experimentally using quantitative real-time polymerase chain reaction. Additionally, the extract’s effects on apoptosis, autophagy, and cell cycle progression were studied experimentally. The aqueous roots extract exhibited selective cytotoxicity against HeLa cells with an IC50 of 12.53 ± 4.983 μg/ml. The network pharmacology analysis identified 25 drug-like compounds targeting 493 unique cervical cancer-associated proteins, forming a protein-protein interaction network of 465 nodes and 2230 edges, and implicated in 178 enriched KEGG pathways. Key targets, including NFΚB1, PIK3CA, HIF1A, STAT3, HSP90AA1, HSP90AB1, PPARG, and ESR1 were experimentally downregulated. Furthermore, S. mannii aqueous roots extract triggered apoptosis through endoplasmic reticulum stress, DNA damage, and activation of the non-transcriptional, P53-mediated mitochondrial apoptotic pathway. Additionally, the extract inhibited hypoxia and autophagy, and induced cell cycle arrest at the G2/M phase, even in the presence of oncogenic HPV proteins (E6 and E7). In conclusion, Solanecio mannii aqueous roots extract demonstrates a “multi-compound, multi-target, multi-pathway” molecular mechanism against cervical cancer.